1996
DOI: 10.2519/jospt.1996.23.5.332
|View full text |Cite
|
Sign up to set email alerts
|

Wobble Board Training After Partial Sprains of the Lateral Ligaments of the Ankle: A Prospective Randomized Study

Abstract: A t the casualty department.. in Scandinavia, 7-10% of the injuries are ankle sprains. This injury is the most common injury in sports (13,20). Eightyfive percent of the sprains involve plantar flexion and supination. In 65% of the sprains, the injury is located only in the anterior talofibular ligament. With more violent inversion force, 20% also suffer damage to the calcaneofibular ligament. The calcaneofibular and the posterior talofibular ligaments are seldom r u p tured alone (14).Traditional sprains of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
150
0
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(162 citation statements)
references
References 14 publications
4
150
0
8
Order By: Relevance
“…Both studies were classified as low-quality studies. At short-term follow-up Wester et al 32 showed a significantly greater improvement in the supervised exercise group. At immediate-and intermediate-term follow-up they failed to demonstrate any statistically significant differences between the treatment groups.…”
Section: Low Quality (N = 6)mentioning
confidence: 99%
See 4 more Smart Citations
“…Both studies were classified as low-quality studies. At short-term follow-up Wester et al 32 showed a significantly greater improvement in the supervised exercise group. At immediate-and intermediate-term follow-up they failed to demonstrate any statistically significant differences between the treatment groups.…”
Section: Low Quality (N = 6)mentioning
confidence: 99%
“…To measure pain they used a visual analogue scale 21 or a dichotomous question. 20,32 Two studies described immediate-term effects, 20,32 2 studies reported shortterm effects, 21,32 all 3 studies reported intermediateterm effects, and 1 study 20 reported long-term effects. Only at short-term follow-up did Oostendorp 21 demonstrate a statistically significant difference between both approaches.…”
Section: Low Quality (N = 6)mentioning
confidence: 99%
See 3 more Smart Citations